2021
DOI: 10.3389/fphar.2021.758468
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation of the Toxic Natural Products From Herbal and Dietary Supplements Leading to Toxicities

Abstract: Currently, herbal and dietary supplements have been widely applied to prevent and treat various diseases. However, the potential toxicities and adverse reactions of herbal and dietary supplements have been increasingly reported, and have gradually attracted widespread attention from clinical pharmacists and physicians. Metabolic activation of specific natural products from herbal and dietary supplements is mediated by hepatic cytochrome P450 or intestinal bacteria, and generates chemical reactive/toxic metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 133 publications
(116 reference statements)
0
19
0
5
Order By: Relevance
“…Normally, the formation of reactive metabolites in herbal medicines or dietary supplements is mediated by hepatic cytochrome P450 or intestinal bacteria. The reactive species formed can covalently bind to cellular macromolecules, including proteins, DNA, and lipids, subsequently triggering toxicity in various manners . The hydrolysis of GE mainly forms GP via the catalysis of intestinal microbiota .…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the formation of reactive metabolites in herbal medicines or dietary supplements is mediated by hepatic cytochrome P450 or intestinal bacteria. The reactive species formed can covalently bind to cellular macromolecules, including proteins, DNA, and lipids, subsequently triggering toxicity in various manners . The hydrolysis of GE mainly forms GP via the catalysis of intestinal microbiota .…”
Section: Introductionmentioning
confidence: 99%
“…Sang et al [ 47 ] found that EGCG can also be oxidized by peroxidase and hydrogen peroxide and then react with cysteine or glutathione, however, studies involving the formation GSH adducts of green tea catechins are still limited. The formation of such adducts scavenges potentially toxic reactive metabolites and reduces their potential for binding to cellular macromolecules [ 48 , 49 ]. From the results presented here, GSH was proven to bind on EGCG and its analogs in the B-ring or D-rings ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is cautioned that potential side effects of interactions between psoralen or isopsoralen with CYP1A2 Furan-containing compounds are often suspected to bring about hepatotoxicity through the formation of reactive intermediates by metabolic activation of CYP450, which subsequently bind to intracellular GSH, DNA, proteins, etc., and induce cytotoxicity (Peterson, 2013;Wang et al, 2021). This theory has undergone some practices (Khojasteh et al, 2020;Wang et al, 2021), for example, furanoid diterpene lactones of disobulbin A, B, C, and F isolated from Dioscorea bulbifera L. were metabolized by CYP3A to cis-enedial intermediates, which were responsible for the observed hepatotoxicity (Li et al, 2016;Wu et al, 2020). In addition, the furan rings of furancontaining components such as rutaevin (Liu, Li, et al, 2020;, columbin (Pei et al, 2020), nomilin (Zhang et al, 2020), etc.…”
Section: Discussionmentioning
confidence: 99%
“…To further clarify the correlation between CYP1A2-mediated metabolism and psoralen/isopsoralen-induced hepatotoxicity, models of induction and inhibition of CYP1A2 in vitro and in vivo were constructed, and the results indicated that the hepatotoxicity of psoralen and isopsoralen was aggravated when CYP1A2 expression was induced, whereas the hepatotoxicity was attenuated when CYP1A2 was inhibited, indicating that CYP1A2 metabolism might be the key trigger for psoralen/ isopsoralen-induced hepatotoxicity. It is cautioned that potential side effects of interactions between psoralen or isopsoralen with CYP1A2 Furan-containing compounds are often suspected to bring about hepatotoxicity through the formation of reactive intermediates by metabolic activation of CYP450, which subsequently bind to intracellular GSH, DNA, proteins, etc., and induce cytotoxicity (Peterson, 2013;Wang et al, 2021). This theory has undergone some practices (Khojasteh et al, 2020;Wang et al, 2021), for example, furanoid diterpene lactones of disobulbin A, B, C, and F isolated from Dioscorea bulbifera L. were metabolized by CYP3A to cis-enedial intermediates, which were responsible for the observed hepatotoxicity (Li et al, 2016;Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation